Membrane Insertion of MoS2 Nanosheets: Fresh vs. Aged - Ye, Rui; Song, Wei; Ou, Xinwen; Gu, Zonglin; Zhang, Dong (Frontiers in Chemistry, 2021)
Fresh two-dimensional molybdenum disulfide (MoS2) absorbs the hydrocarbon contaminations in the ambient air and makes surface aging. To understand how the surface aging influences the interactions between MoS2 and biomolecules is important in the biomedical applications. Here, employing all-atom molecular dynamics simulations, we investigated the interactions of the fresh and aged MoS2 nanosheets with the lipid membranes of different components. Our results demonstrate that both the fresh and aged MoS2 nanosheets can spontaneously insert into the bilayer membranes. However, the fresh MoS2 nanosheet displays significantly stronger interaction and then has a larger penetration depth than the aged counterpart, regardless of the lipid components. The calculations of potential mean forces through the umbrella sampling further confirm that the insertion of fresh MoS2 into the lipid membranes is more energetically favorable. Moreover, we found that the fresh MoS2 nanosheet can cause a larger damage to the integrity of lipid membranes than the aged one. This work provides insightful understandings of the surface-aging-dependent interactions of the MoS2 nanosheets with biomembranes, which could facilitate the design of novel MoS2-based nanodevices with advanced surface properties.